The manifestation of self-hatred in Mabvumira eNhetembo - Tambanewenyu, Rutendo (Midlands State University, 2018)
This study is in the area of literal studies. This study focuses on the Manifestation of selfhatred in Mabvumira enhetembo published by Literature Bureau during colonial period. This study is driven by Afrocentricity that seeks to revive and resurrect African culture and African philosophies of life. Couched and guided with Afrocentricity, the study also relies on the information obtained from respondents acquired through interviews and questionnaires. The research participants include of poets, academics, publishing houses and students. A strong background was laid, as the study examined the role of poets in Shona society, the channels that propagated self-hatred in Africa and the manifestation of self-hatred in Africa. The channels that propagated self-hatred in Africa includes of colonial education, Christianity and literature bureau. The study argues that, poets must move away from white supremacist and appreciate African culture thus putting it at the centre. This entails that Shona literature must enable people to fight against their struggles and revive African cultures. More so, the study argues that Shona people must appreciate and celebrate their African philosophies of life and culture. The study went further to establish that, families in the Shona society are critical to nation building. The researcher hopes that this study will contribute in the resurrecting and reviving of African culture.